Polycrystalline transistor with multiple thresholds. (January 2019) - Kabir, HM Dipu; Chan, Mansun
Abstract: This paper presents the co-existence of multiple thresholds in a single polycrystalline transistor with examples, reasons, and fabrication results. Polycrystalline transistors are traditionally represented and modeled as a transistor of a single threshold voltage. During the characterization, researchers often find that a polycrystalline transistor exhibits multiple thresholds. We first exemplify existences of two/multiple threshold voltages at current-voltage characteristics of several published literature. Then we theoretically prove the reason for the co-existence of multiple thresholds in a polycrystalline transistor. Finally, we present our fabricated organic polycrystalline transistors exhibiting multiple thresholds. This work may help future device researchers in studying devices and researching for novel applications.